(untitled) (Al-Qamar, 2021)
The Holy Book of Allah the Almighty was revealed to the Last Prophet Muhammad and is known as the Quran (PBUH). Not a single word in the Quran has been altered or deleted; it is the exact words of Allah. The Quran is the single most significant source to consider to comprehend the essence of the Islamic religion and the directives and orders of Allah Almighty. Being a book for both men and women, young and elderly, literate and uneducated, and in short, a book of instruction for all humans, for all periods, and all regions of the world, is the Quran’s singularity and beauty. Islam has granted rights to every living thing, as was already mentioned. Islamic legal doctrine is very explicit regarding human beings’ rights. Transgender people have undoubtedly received numerous rights indirectly because of Islam. They have access to the same rights as other mainstream Muslims in society. They can trade, pray, perform the Hajj, become teachers, and even imams. Islam accepts transgender people as normal human beings, not as cursed beings, in contrast to other societies and cultures. Islam treats transgender people the same way it would treat a typical male or female.